Peran Manajemen Humas dalam Mempromosikan Integritas Sekolah SMK Tritech Informatika Kepada Masyarakat Kota Medan - Akmal, Rifqy Ikhsanul; Ritonga, Muhammad Husni; Jailani, Muhammad (Communication & Social Media, 2023)
This research aims to investigate the role of public relations management in promoting the integrity of SMK Tritech Informatika to the community in Medan City. A qualitative descriptive research method was employed, utilizing The Excellence Theory as the theoretical framework. Data were collected through observations, interviews, and documentation. Data analysis involved the process of data reduction, data presentation, and drawing conclusions. The findings of the study indicate that there are three steps that should be undertaken by public relations management to promote the school's integrity, namely understanding the internal and external conditions of the school, improving the physical and non-physical aspects of the school, and introducing the school to the community while establishing collaborations with relevant institutions. These findings have significant implications for the development of effective public relations management strategies in enhancing the school's image and reputation in the eyes of the public. It is expected that the results of this research will contribute to the understanding and practice of educational public relations management and serve as a reference for other schools in enhancing integrity and fostering positive relationships with the surrounding community.